Effective diffusivity in yacon potato cylinders during drying - Cícera G. C. de Lisboa; Josivanda P. Gomes; Rossana M. F. de Figueirêdo; Alexandre J. de M. Queiroz; Adelino de M. G. Diógenes; João C. S. de Melo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The aim of this study was to obtain the effective diffusivity of yacon potato in fixed-bed dryer at different temperatures (50, 60 and 70 ºC) and drying air velocities (1.0, 1.5 and 2.0 m s-1). Non-linear regression analysis was performed by the Quasi-Newton method using the program Statistica 7.0, where the parameters of the models were estimated as a function of the drying air temperature. Approximation of Diffusion, Two Terms, Henderson & Pabis, and Page models fitted well the experimental data. Drying air temperature and speed influenced the drying time of the samples. The effective diffusivity increased with increasing temperature, ranging from 1.18 x 10-9 to 2.15 x 10-9 m2 s-1.